The Relationship between Tourism Development, Satisfaction, Support to Tourism and Tourism Entrepreneurship in Emerging Tourism Destination: Residents’ Perspective - Akay, Bayram (Journal of Tourism Management Research, 2022)
The purpose of this study is to research the relationship between tourism development in the province of Burdur, satisfaction, support to tourism development and tourism entrepreneurship. The research model developed was based upon the theory of social change and was tested by using PLS-SEM. The data were obtained from 390 persons residing in the province of Burdur by using the survey method. The findings have revealed significant relationships between positive economic and sociocultural effect in tourism development and satisfaction by tourism development, support for tourism development and tourism entrepreneurship. No relationship between positive environmental effect, negative economic, sociocultural and environmental effect, and satisfaction by tourism development was confirmed. The results are coherent with the theory of social change in terms of indicating that the residents of Burdur perceive much the benefits in tourism development, but not yet the costs. Moreover, the findings of this study reveal the tourism entrepreneurship role of the residents, although the tourism development studies neglect the tourism entrepreneurship of the residents on a large scale.